2013
DOI: 10.1007/s00405-013-2702-y
|View full text |Cite|
|
Sign up to set email alerts
|

Diagnostic value of cone-beam CT in histologically confirmed otosclerosis

Abstract: This retrospective case review was performed with the aim to asses the value of cone-beam computed tomography (CBCT) in the preoperative diagnosis of otosclerosis. A total of 32 patients with histologically confirmed stapedial otosclerosis, who underwent unilateral stapedectomies were analyzed. Preoperative temporal bone CBCT scans were performed in all cases. CBCT imaging was characterized by a slice thickness of 0.3 mm and multiplanar image reconstruction. Histopathologic examination of the removed stapes fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 24 publications
1
20
0
2
Order By: Relevance
“…Presently, HRCT has 80% to 91% sensitivity for detection of otosclerotic foci. 4,7,18 Our neuroradiology and otology detection rates were comparable to the aforementionec published rates. The community radiologist detection rates were somewhat lower, highlighting the variation of disease detection.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Presently, HRCT has 80% to 91% sensitivity for detection of otosclerotic foci. 4,7,18 Our neuroradiology and otology detection rates were comparable to the aforementionec published rates. The community radiologist detection rates were somewhat lower, highlighting the variation of disease detection.…”
Section: Discussionsupporting
confidence: 86%
“…More recently, high-resolution computed tomography (HRCT) has been utilized to evaluate the temporal bone in the setting where conductive hearing loss is complicated by possible infection or trauma. 1,4,5 Multiple clinical studies comparing radiologic diagnosis of otosclerosis based on HRCT with the diagnosis based on history, examination, audiology, and intraoperative findings have shown good sensitivity, ranging from 80% to 91%, when scans are reviewed by neuroradiologists. 4,6,7 The cochlear aqueduct (CA) is a bony duct connecting the scala tympani and associated perilymphatic space with the subarachnoid space.…”
Section: Introductionmentioning
confidence: 99%
“…Prior literature has suggested that MDCT and CBCT are limited in cases of tiny foci less than 1 mm, superficial foci, inactive disease and density variation of less than 200 Hounsfield units (HUs). 1922 In addition, CBCT has been found to have a 0% sensitivity for detection of otosclerosis in the sclerotic phase; however, detection was based on a visual grading system with no standardized measurement techniques utilized. 19 As in our study, Swartz et al described the presence of a bony excrescence or bulging contour of the otic capsule anterior to the oval window as a helpful finding in otosclerosis; 23 however, the interval improvement in MDCT technology now enables reproducible quantitative measurements in standardized planes improving accuracy and reproducibility.…”
Section: Discussionmentioning
confidence: 99%
“…1922 In addition, CBCT has been found to have a 0% sensitivity for detection of otosclerosis in the sclerotic phase; however, detection was based on a visual grading system with no standardized measurement techniques utilized. 19 As in our study, Swartz et al described the presence of a bony excrescence or bulging contour of the otic capsule anterior to the oval window as a helpful finding in otosclerosis; 23 however, the interval improvement in MDCT technology now enables reproducible quantitative measurements in standardized planes improving accuracy and reproducibility. A recent systematic review suggests that high-resolution CT has a low sensitivity of 58%, high specificity of 95%, and a high PPV of 92%, but is limited in sub-millimeter disease, retrofenestral disease and dense sclerotic lesions.…”
Section: Discussionmentioning
confidence: 99%
“…A sebészeti szempontból kiemelt struktúrák legalább olyan jól láthatók, mint multislice CT-vel [16,17]. Szövettanilag aktív otoscleroticus gócok 100%-os szenzitivitással kimutathatók CBCT-vel [18,19].…”
Section: áBra)unclassified